Rapid viral diagnosis and ambulatory management of suspected COVID-19 cases presenting at the infectious diseases referral hospital in Marseille, France, - January 31st to March 1st, 2020: A respiratory virus snapshot. Issue 36 (July 2020) - Amrane, Sophie; Tissot-Dupont, Hervé; Doudier, Barbara; Eldin, Carole; Hocquart, Marie; Mailhe, Morgane; Dudouet, Pierre; Ormières, Etienne; Ailhaud, Lucie; Parola, Philippe; Lagier, Jean-Christophe; Brouqui, Philippe; et al.
Abstract: Background: Rapid virological diagnosis is needed to limit the length of isolation for suspected COVID-19 cases. Method: We managed the first 280 patients suspected to have COVID-19 through a rapid care circuit and virological diagnosis in our infectious disease reference hospital in Marseille, France. Rapid viral detection was performed on sputum and nasopharyngeal samples. Results: Over our study period, no SARS-CoV-2 was detected. Results were obtained within approximately 3 h of the arrival of patient samples at the laboratory. Other viral infections were identified in 49% of the patients, with most common pathogens being influenza A and B viruses, rhinovirus, metapneumovirus and common coronaviruses, notably HKU1 and NL63. Conclusion: Early recognition of COVID-19 is critical to isolate confirmed cases and prevent further transmission. Early rule-out of COVID-19 allows public health containment measures to be adjusted by reducing the time spent in isolation.